2018
DOI: 10.1049/iet-sen.2017.0026
|View full text |Cite
|
Sign up to set email alerts
|

How test suites impact fault localisation starting from the size

Abstract: Although a test suite is indispensable for conducting effective fault localisation, not much work has been done to study how the test suite impacts fault localisation. This study presents a systematic study for a deeper understanding of their relation. Specifically, the authors' study reveals an interesting fact that there is no strong correlation between localisation effectiveness and the size of the test suite. Furthermore, they show that, in a test suite, (i) the passing test cases that do not execute the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 60 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…Following the general convention [23,24,31,40], all test suites are generated with random algorithms concerning the specific features being tested, then filtered to assure that no MR is violated when running on the correct version of subject programs, and finally sampled to a scale of 1000 test cases except SeqMap for an efficient experiment timeline.…”
Section: Test Suite Generationmentioning
confidence: 99%
“…Following the general convention [23,24,31,40], all test suites are generated with random algorithms concerning the specific features being tested, then filtered to assure that no MR is violated when running on the correct version of subject programs, and finally sampled to a scale of 1000 test cases except SeqMap for an efficient experiment timeline.…”
Section: Test Suite Generationmentioning
confidence: 99%
“…suite reduction techniques to lower debugging expenses, some recent studies have also investigated the impact of test suites on fault localization [62,63]. For example, as Fu et al argued, if the number of successful test cases is too large, the noise will be introduced into the fault localization process [64].…”
Section: Namementioning
confidence: 99%
“…To initiate the realization of the basic idea, we should first identify those data related to the weak but beneficial experience. The research 15,16 has found failing test cases are always beneficial (or at least safe) for fault localization effectiveness.16 However, failing test cases are much less than passing test cases. It means that the experience learned from failing test cases is weak.…”
Section: Examplementioning
confidence: 99%
“…13,14 It will affect the accuracy of the learned localization model. Furthermore, the research 15 has found that the effect of including more passing test cases is unpredictable and adding passing test cases could both improve or degrade diagnostic accuracy. Thus, the bias to passing test cases may worsen the learning process of an effective localization model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation